Liver type 1 innate lymphoid cells lacking IL-7 receptor are a native killer cell subset fostered by parenchymal niches - Asahi, Takuma; Abe, Shinya; Cui, Guangwei; Shimba, Akihiro; Nabekura, Tsukasa; Miyachi, Hitoshi; Kitano, Satsuki; Ohira, Keizo; Dijkstra, Johannes M; Miyazaki, Masaki; Shibuya, Akira; Ohno, Hiroshi; et al. (eLife, 2023)
Group 1 innate lymphoid cells (G1-ILCs), including circulating natural killer (NK) cells and tissue-resident type 1 ILCs (ILC1s), are innate immune sentinels critical for responses against infection and cancer. In contrast to relatively uniform NK cells through the body, diverse ILC1 subsets have been characterized across and within tissues in mice, but their developmental and functional heterogeneity remain unsolved. Here, using multimodal in vivo approaches including fate-mapping and targeting of the interleukin 15 (IL-15)-producing microenvironment, we demonstrate that liver parenchymal niches support the development of a cytotoxic ILC1 subset lacking IL-7 receptor (7 R − ILC1s). During ontogeny, fetal liver (FL) G1-ILCs arise perivascularly and then differentiate into 7 R − ILC1s within sinusoids. Hepatocyte-derived IL-15 supports parenchymal development of FL G1-ILCs to maintain adult pool of 7 R − ILC1s. IL-7R + (7R + ) ILC1s in the liver, candidate precursors for 7 R − ILC1s, are not essential for 7 R − ILC1 development in physiological conditions. Functionally, 7 R − ILC1s exhibit killing activity at steady state through granzyme B expression, which is underpinned by constitutive mTOR activity, unlike NK cells with exogenous stimulation-dependent cytotoxicity. Our study reveals the unique ontogeny and functions of liver-specific ILC1s, providing a detailed interpretation of ILC1 heterogeneity.